Correction: Luzardo et al. Integrating Conservation and Community Engagement in Free-Roaming Cat Management: A Case Study from a Natura 2000 Protected Area. Animals 2025, 15, 429 - Octavio P. Luzardo; Andrea Hansen; Beatriz Martín-Cruz; Ana Macías-Montes; María del Mar Travieso-Aja (Animals, 2025)
In the original publication [...]